2008
DOI: 10.1017/s0033291707002553
|View full text |Cite
|
Sign up to set email alerts
|

Memory and metamemory in schizophrenia: a liberal acceptance account of psychosis

Abstract: Background. In previous studies we suggested that liberal acceptance (LA) represents a fundamental cognitive bias in schizophrenia and may explain why patients are more willing to accept weak response alternatives and display overconfidence in incorrect responses. The aim of the present study was to test a central assumption of the LA account : false alarms in schizophrenia should be particularly increased when the distractor-target resemblance is weak relative to a control group.Method. Sixty-eight schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 28 publications
9
85
1
1
Order By: Relevance
“…The results from this study do not point to a specific cognitive mechanism affecting evidence integration, although our previously proposed concepts of liberal acceptance (LA; Moritz et al 2007Moritz et al , 2008 and/or hypersalience of evidencehypothesis (EVH) matches (Speechley et al 2010;Balzan et al 2012Balzan et al , 2013) may underlie impairment in evidence integration on the BADE task. For example, the LA account would suggest that, in highly delusional patients, all BADE interpretations are considered somewhat plausible initially, and so the true interpretation is not fully accepted and the absurd/lure interpretations are not fully dismissed, and a definitive decision is delayed.…”
Section: Comparisons With Previous Studiescontrasting
confidence: 75%
“…The results from this study do not point to a specific cognitive mechanism affecting evidence integration, although our previously proposed concepts of liberal acceptance (LA; Moritz et al 2007Moritz et al , 2008 and/or hypersalience of evidencehypothesis (EVH) matches (Speechley et al 2010;Balzan et al 2012Balzan et al , 2013) may underlie impairment in evidence integration on the BADE task. For example, the LA account would suggest that, in highly delusional patients, all BADE interpretations are considered somewhat plausible initially, and so the true interpretation is not fully accepted and the absurd/lure interpretations are not fully dismissed, and a definitive decision is delayed.…”
Section: Comparisons With Previous Studiescontrasting
confidence: 75%
“…For example, a number of studies, recently summarized in two meta-analyses [2,3], demonstrated that patients with psychotic disorders and particularly those who experience delusions, jump to conclusions. Another literature indicates that patients are overconfident in their false judgements pertaining to memory, perception and social cognition [4,5]. Finally, a number of studies indicate that patients with psychosis are less open to counter-arguments, even for delusion-neutral scenarios [6].…”
Section: Cognitive Biases In Psychosismentioning
confidence: 99%
“…4,9 A second construct pertains to a certain incorrigibility, which manifests as disturbed integration of disambiguating or disconfirmatory evidence 7,[10][11][12] and increased confidence in false judgments. 13,14 Evidence gathering and incorrigibility have been shown to be largely independent from each other, 15,16 though intercorrel ated to some extent. 16,17 Interestingly, current work suggests that they respond differently to antipsychotic medication in clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…The jumping-to-conclusions bias, for example, does not appear to be affected by antipsychotic medication in a consistent manner, [18][19][20] whereas overconfidence in errors has been suggested to improve with antipsychotic treatment. 14,16,21 This issue is highly relevant to the treatment of psychotic disorders in light of the prominent account that delusions result from a dopaminergic dysfunction in the mesolimbic system. 22 If delusion-associated reasoning biases are differentially affected by antipsychotic medication, it is possible that they represent different stages of delusion formation and/or maintenance, not all of which are dependent on the dopamine system.…”
Section: Introductionmentioning
confidence: 99%